2017
DOI: 10.1002/apj.2145
|View full text |Cite
|
Sign up to set email alerts
|

A three‐dimensional CFD and experimental study to optimize naturally air‐cooled electronic equipment enclosure: Effects of inlet height, heat source position, and buoyancy on mean rise in temperature

Abstract: The major reason behind failure of electronic components is the rise in temperature. To optimize design of naturally cooled electronic equipment enclosure, a detailed experimental study and a computational fluid dynamics (CFD) analysis were performed. Commercially available software, ANSYS Fluent, was used for CFD analysis. The three-dimensional form of Navier-Stokes equations was used to solve the problem computationally. Aluminium enclosure having dimensions of 40 cm × 40 cm × 21 cm and thermal conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Ali Riaz et al studied effect of heat source height inside the ventilated enclosure on mean rise in temperature numerically. This study suggested that heat source should be at minimum height relative to the base of enclosure or at maximum height relative to the outlet position of the enclosure to achieve maximum cooling [2,3] . Basavaraj Kusammanavar et al numerically studied the effect of heat source position on natural convection in a square cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Ali Riaz et al studied effect of heat source height inside the ventilated enclosure on mean rise in temperature numerically. This study suggested that heat source should be at minimum height relative to the base of enclosure or at maximum height relative to the outlet position of the enclosure to achieve maximum cooling [2,3] . Basavaraj Kusammanavar et al numerically studied the effect of heat source position on natural convection in a square cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Semen et al [4] have simulated the problem of conjugate natural convection combined with surface thermal radiation in a two-dimensional enclosure, and also in three-dimensional enclosures [5,6]. Riaz et al [7] have optimized a naturally air-cooled electronic equipment using CFD.…”
Section: Introductionmentioning
confidence: 99%